Activated carbon, silicon-carbon composite material and preparation method and application thereof

The activated carbon is prepared by spray-drying the coated carbon nanotubes and using flash joule heating technology to prepare silicon-carbon composite materials, which solves the problems of process complexity and insufficient performance in traditional processes, and realizes the preparation of high-performance silicon-carbon composite materials.

CN119706832AActive Publication Date: 2025-03-28SHANGHAI SHANSHAN NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411899240.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

In the prior art, porous carbon materials prepared by Joule heating require subsequent activation treatment, which increases process complexity. In addition, the silicon-carbon composite materials have defects such as electrode cracks, performance attenuation and insufficient conductivity caused by volume expansion during charging and discharging.

Method used

Through spray drying, the resin-coated carbon nanotubes and activator was designed, and flash joule heating technology was used to quickly prepare activated carbon with high specific surface area and large amounts of micropores in one step for the preparation of silicon-carbon composite materials in the gas phase.

Benefits of technology

Silicon-carbon composite materials with low expansion, high first-time reversible capacity, high first-time Coulomb efficiency, excellent rate performance and stability were obtained, solving the problems of insufficient process complexity and performance in traditional processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses activated carbon, a silicon-carbon composite material and a preparation method and application thereof. The preparation method of the activated carbon comprises the following steps: S1, carrying out spray drying on a suspension of carbon nanotubes, an activating agent and a resin raw material to obtain an activated carbon precursor; wherein the mass ratio of the carbon nano tube to the resin raw material is (0.4-1.2): 40; the mass ratio of the activating agent to the resin raw material is (30-60): 40; and S2, carrying out flash evaporation Joule heating on the activated carbon precursor. According to the preparation method of the activated carbon, the resin-coated carbon nanotubes and the activating agent are designed through spray drying, and the flash evaporation Joule heating technology is adopted, so that the activated carbon with high specific surface area and a large number of micropores can be rapidly prepared in one step; further, the silicon-carbon composite material with low expansion, high first reversible capacity, high first coulombic efficiency, excellent rate capability and stability is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of silicon-carbon composite materials, and in particular to activated carbon, a silicon-carbon composite material, and a preparation method and application thereof. Background Art

[0002] The gas phase silicon-carbon composite material uses activated carbon as a substrate, and uses a gas phase silicon source to vapor-deposit nano-silicon to form a silicon-carbon composite material in which nano-silicon is embedded in the pores of activated carbon. Due to its unique structural design, this material exhibits excellent cycle stability, low expansion rate and high specific capacity, and is the focus of future research and development of negative electrode materials for lithium-ion batteries. In the preparation process of gas phase silicon-carbon composite materials, activated carbon is a key raw material, and its mass share in the final product can usually reach 40%-50%. Therefore, the preparation of activated carbon has a significant impact on gas phase silicon-carbon materials.

[0003] The preparation process of activated carbon mainly includes high-temperature carbonization and activation stages. Most existing heating methods use kiln radiation heating to heat the material. However, this method has problems such as long heating time, high energy consumption, and complex operation. Therefore, it is urgent to explore more efficient and rapid heating technology.

[0004] Flash Joule heating is a new type of ultrafast heating technology. Through program control, the material can be quickly heated to a high temperature within a few seconds. In recent years, patents have been used to synthesize high-value activated carbon materials using flash Joule heating technology. For example, patent CN117585667A uses flash Joule heating to convert waste resin into nano-spherical carbon materials; CN114408919A quickly carbonizes coconut shells through high-temperature thermal shock, and activates and cleans them with KOH to finally obtain carbon materials for supercapacitors; CN113307267A mixes coal tar with a pore-forming agent, performs Joule heating, and obtains porous carbon materials by washing. However, these porous carbon materials prepared by Joule heating usually require subsequent activation treatment, which increases the complexity of the production process. At the same time, the huge volume change of silicon-carbon composite materials during the charge and discharge cycle will induce the accumulation of stress inside the electrode to produce cracks, resulting in electrode pulverization, separation of active materials from the current collector, and then performance attenuation, poor cycle stability, and poor conductivity of silicon, which is not conducive to the release of battery capacity under high current. Excellent porous carbon structure design has a significant impact on the performance of silicon-carbon composite materials. For example, patents CN117038989A and CN114122370B introduce carbon nanotubes into porous carbon microspheres to improve the conductivity and expansion rate of silicon-carbon composite materials. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the fact that the porous carbon materials prepared by Joule heating in the prior art need subsequent activation treatment, which increases the complexity of the process, and the silicon-carbon composite materials have defects such as electrode cracks, performance attenuation and insufficient conductivity caused by volume expansion during the charge and discharge process, and provide an activated carbon, a silicon-carbon composite material and a preparation method and application thereof. When the activated carbon is used to prepare the silicon-carbon composite material in the gas phase, the silicon-carbon composite material exhibits excellent first reversible capacity, first coulomb efficiency, rate performance and expansion rate. The preparation method of the activated carbon is to spray-dry the resin-coated carbon nanotubes and the activator, and adopt the flash Joule heating technology, so as to quickly prepare the activated carbon with high specific surface area and a large number of micropores in one step, and then obtain the silicon-carbon composite material with low expansion, high first reversible capacity, high first coulomb efficiency, excellent rate performance and stability.

[0006] The present invention solves the above technical problems through the following technical solutions:

[0007] The present invention provides a method for preparing activated carbon, which comprises the following steps:

[0008] S1. spray drying a suspension of carbon nanotubes, an activator and a resin raw material to obtain an activated carbon precursor;

[0009] Wherein, the mass ratio of the carbon nanotubes to the resin raw material is (0.4-1.2):40;

[0010] Wherein, the mass ratio of the activator to the resin raw material is (30-60):40;

[0011] S2. Performing flash Joule heating on the activated carbon precursor.

[0012] In this embodiment, the suspension is conventional in the art, for example, carbon nanotubes, activator and resin raw material are dispersed in a solvent, and the mixture of solid dispersed phase and liquid is called a suspension.

[0013] Preferably, the activator is a metal zinc salt and / or a polymer template.

[0014] More preferably, the metal zinc salt comprises a combination of one or more of zinc acetate, zinc chloride, zinc oxide and zinc acetylacetonate.

[0015] More preferably, the polymer template comprises one or more combinations of polystyrene, PEO-PPO-PEO triblock copolymer, PS-P4VP diblock copolymer, polyethylene oxide PEO, polyvinyl pyrrolidone PVP, polymethyl methacrylate PMMA and polyvinyl alcohol PVA.

[0016] More preferably, the PEO-PPO-PEO triblock copolymer is preferably a combination of one or more of Pluronic® F127, Pluronic® P123 and Pluronic® F108.

[0017] Further preferably, the activator is zinc acetate or Pluronic® F127.

[0018] In this scheme, metal zinc salts (such as zinc acetate) or polymer templates (such as Pluronic® F127) are used as activators to help regulate the size and distribution of pores during the formation of activated carbon, thereby improving the specific surface area and pore volume.

[0019] Preferably, the resin raw material is a combination of one or more of phenolic resin, polystyrene, polyacrylonitrile, resorcinol-formaldehyde resin and polyimide, for example, phenolic resin.

[0020] Preferably, the solvent of the suspension of the carbon nanotubes, the activator and the resin raw material is a combination of one or more of anhydrous ethanol, NN dimethylamide, dimethyl sulfoxide, toluene and pure water, for example, anhydrous ethanol.

[0021] Preferably, the diameter of the carbon nanotube is 0.5-10 nm, such as 1-2 nm.

[0022] Preferably, the length of the carbon nanotubes is 1 μm-30 μm, such as 5-15 μm.

[0023] Preferably, the mass ratio of the carbon nanotubes to the resin raw material is (0.5-1.0):40.

[0024] Preferably, the mass ratio of the activator to the resin raw material is (40-60):40.

[0025] Preferably, in the suspension, the volume ratio of solid to liquid is 5%-30%, for example 20%.

[0026] Preferably, the inlet air temperature of the spray drying is 80-200°C, such as 130-200°C.

[0027] Preferably, the outlet air temperature of the spray drying is 60-100°C, such as 80-100°C.

[0028] Preferably, the feed rate of the spray drying is 0.01-1 L / h, preferably 0.5 L / h.

[0029] Preferably, the spray drying atmosphere is compressed air or an inert atmosphere.

[0030] In this scheme, the morphology and particle size of the particles can be precisely controlled by spray drying, especially under the control of temperature and atmosphere, so that a precursor with a predetermined specific surface area and pore structure can be effectively obtained.

[0031] More preferably, the inert atmosphere is a combination of one or more of nitrogen, argon and helium.

[0032] Preferably, the D50 of the spray-dried droplets is 10-100 μm, such as 70 μm.

[0033] Preferably, D10 of the activated carbon precursor is 1.5-5 μm, for example 3.2 μm.

[0034] Preferably, the D50 of the activated carbon precursor is 3-15 μm, for example 4.7 μm.

[0035] Preferably, the D90 of the activated carbon precursor is 5-50 μm, for example 6.5 μm.

[0036] Preferably, the activated carbon precursor is spherical.

[0037] Preferably, in the activated carbon precursor, the interior of the resin raw material contains a number of the carbon nanotubes, and the surface of the resin raw material contains a network structure formed by a number of the carbon nanotubes.

[0038] Preferably, the terminal temperature of the flash Joule heating is 800-3500°C, for example 1000°C.

[0039] Preferably, the voltage of the flash Joule heating is 50-400V, for example 200V.

[0040] Preferably, the flash Joule heating rate is 1000-8000°C / s.

[0041] Preferably, the continuous power-on time of the flash Joule heating is 0-100s, for example 10s.

[0042] Preferably, the atmosphere for the flash Joule heating is a vacuum or inert atmosphere.

[0043] In this embodiment, the operation of the flash Joule heating may be conventional in the art, for example, using electric current to heat the material within milliseconds to microseconds.

[0044] Preferably, the inert atmosphere is a combination of one or more of argon, nitrogen, helium and neon, such as argon.

[0045] More preferably, the vacuum degree of the flash Joule heating is 1 mTorr-10 Torr, for example, 1.2 Torr.

[0046] Preferably, the flash Joule heating reaction equipment is a flash Joule heating device.

[0047] The present invention also provides activated carbon, which is prepared by the above-mentioned preparation method.

[0048] Preferably, the specific surface area of ​​the activated carbon is 1450-1900m 2 / g, such as 1459.7, 1520.1, or 1812.8m 2 / g.

[0049] Preferably, the total pore volume of the activated carbon is 1.0-1.2 cm 3 / g, such as 1.02 or 1.15 cm 3 / g.

[0050] Preferably, the average pore size of the activated carbon is 0.8-1.8 nm, such as 0.83, 0.88 or 1.76 nm.

[0051] The present invention also provides a method for preparing a silicon-carbon composite material, which specifically comprises the following steps: vapor-depositing the above-mentioned activated carbon and silicon source to obtain the silicon-carbon composite material.

[0052] Preferably, the silicon-carbon composite material comprises the activated carbon and the silicon source deposited in the pores of the activated carbon.

[0053] Preferably, the silicon source is in gaseous state.

[0054] Preferably, the silicon source is a combination of one or more of monosilane, disilane and silane derivatives, such as monosilane.

[0055] Preferably, the flow rate of the silicon source is 0.1-30 L / min, for example 0.8 L / min.

[0056] Preferably, the atmosphere for the vapor deposition is an inert atmosphere.

[0057] More preferably, the inert atmosphere is a combination of one or more of nitrogen, argon and helium, such as argon.

[0058] More preferably, the flow rate of the inert atmosphere is 0.1-40 L / min, such as 0.4 L / min.

[0059] Preferably, the vapor deposition reaction equipment is a rotary kiln or a fluidized bed, such as a fluidized bed.

[0060] Preferably, the reaction temperature of the vapor deposition is 400-700°C, for example 600°C.

[0061] Preferably, the reaction time of the vapor deposition is 2-12 h, such as 5 h or 10 h.

[0062] Preferably, the heating rate from room temperature to the reaction temperature of the vapor deposition is 1-5°C / min, for example 3°C / min.

[0063] Preferably, the gas pressure of the vapor deposition is 100-11000 Pa, such as 1 MPa.

[0064] Preferably, after the vapor deposition, a carbon coating step is also included.

[0065] Further preferably, the carbon source used for the carbon coating is a hydrocarbon mixture, more preferably a combination of one or more of methane, ethane, propane, isopropane, butane, isobutane, ethylene, propylene, acetylene, butene and natural gas, such as acetylene.

[0066] More preferably, the flow rate of the carbon source used for the carbon coating is 0.1-40 L / min, such as 0.2 L / min.

[0067] More preferably, the carbon coating atmosphere is an inert atmosphere, and more preferably the inert atmosphere is a combination of one or more of nitrogen, argon and helium, such as argon.

[0068] More preferably, the flow rate of the inert atmosphere is 0.1-40 L / min, such as 0.4 L / min.

[0069] More preferably, the carbon coating method is gas phase coating.

[0070] More preferably, the reaction temperature of the carbon coating is 400-700°C, for example 600°C.

[0071] More preferably, the carbon coating reaction time is 2-24 h, such as 3 h or 6 h.

[0072] More preferably, after the carbon coating, the thickness of the carbon coating layer of the obtained silicon-carbon composite material is 2-50 nm, for example, 30 nm.

[0073] In this solution, the carbon coating is carried out by vapor deposition to deposit the carbon source on the surface of the activated carbon to form a carbon coating layer, thereby reducing the specific surface area of ​​the material, avoiding exposure of silicon, reducing the occurrence of side reactions, and improving the first coulombic efficiency, conductivity and cycle stability of the material.

[0074] The present invention also provides a silicon-carbon composite material, which is prepared by the above-mentioned method for preparing the silicon-carbon composite material.

[0075] Preferably, the silicon content of the silicon-carbon composite material is 44-53 wt%, such as 51.9, 52.2 and 52.4 wt%.

[0076] The present invention also provides an application of the silicon-carbon composite material as described above in the preparation of battery pole pieces.

[0077] The positive and progressive effects of the present invention are:

[0078] (1) Compared with the activated carbon prepared by the conventional rotary kiln, the activated carbon prepared by the flash Joule heating method of the present invention has a larger specific surface area, a smaller average pore size and a higher pore size concentration.

[0079] (2) Compared with the silicon-carbon composite material without carbon nanotubes, the silicon-carbon composite material containing carbon nanotubes of the present invention not only exhibits superior conductivity and lower energy consumption, but also improves rate performance and reduces expansion rate. This is attributed to the high conductivity of carbon nanotubes and the network structure formed by them, which improves the electrochemical performance and mechanical stability of the silicon-carbon composite material.

[0080] (3) The battery made of the silicon-carbon negative electrode material of the present invention has obvious advantages in electrochemical performance. The lithium-ion battery made of the silicon-carbon negative electrode material of the preferred embodiment has an initial reversible capacity of up to 2093.2 mAh / g, an initial coulombic efficiency of up to 91.3%, a 2C capacity of up to 1437.7 mAh / g, and a 1.5-cycle expansion rate of only 81.5%. Although the expansion rate is slightly high, the overall performance is relatively balanced, especially in terms of initial reversible capacity and rate performance, showing good comprehensive electrochemical performance. DETAILED DESCRIPTION

[0081] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0082] In the following examples and comparative examples, the carbon nanotubes have a diameter of 1-2 nm and a length of 5-15 μm, and are NTP8012 from Shenzhen Nanoport Co., Ltd.

[0083] In the following examples and comparative examples, the phenolic resin is derived from the 4123B model of Zetian Chemical Co., Ltd.

[0084] In the following examples and comparative examples, the flash Joule heating device is derived from the Joule heat pipe furnace of Hefei Yuanzui Technology Co., Ltd.

[0085] In the following examples and comparative examples, the fluidized bed apparatus is derived from the OTF-1200X-S-FB model of Hefei Kejing.

[0086] In the following examples and comparative examples, the Pluronic® F127 is derived from the P2243 model of Sigma-Aldrich Company, and has a molecular weight of 12600 g / mol.

[0087] Example 1

[0088] S1. 10g of carbon nanotubes, 400g of zinc chloride, 400g of phenolic resin, and 3200mL of anhydrous ethanol were prepared into a uniform suspension, and the suspension was spray-dried to obtain a spherical activated carbon precursor. Spray drying used a nitrogen atmosphere, the D50 of the spray-dried droplets was 70μm, the inlet air temperature was 130℃, the outlet temperature was 80℃, and the feed rate was 0.5L / h. In the spherical activated carbon precursor obtained after spray drying, the phenolic resin was spherical, part of the carbon nanotubes was located inside the phenolic resin and intertwined with the phenolic resin, and the other part formed a network structure on the surface of the phenolic resin. The particle size of the spherical activated carbon precursor was D10 of 3.2μm, D50 of 4.7μm, and D90 of 6.5μm.

[0089] S2. Place the spherical activated carbon precursor in a flash Joule heating device with a vacuum degree of 1.2 Torr and a voltage of 200 V. Heat to 1000°C in 1 second and keep the power on for 10 seconds. The device operates in an inert atmosphere of argon and collects the activated carbon powder after cooling to room temperature.

[0090] S3. The collected activated carbon powder was placed in a fluidized bed apparatus, and the temperature was raised from room temperature to 600°C at a heating rate of 5°C / min at 1MPa. At 600°C, the monosilane flow rate was 0.8L / min and the nitrogen flow rate was 0.4L / min, and silane deposition was performed for 5 hours. During this process, silicon was deposited into the pores of the activated carbon.

[0091] S4. In the same device, maintain 600°C, a nitrogen flow rate of 0.4 L / min, an acetylene flow rate of 0.2 L / min, and deposit for 3 hours, and continue carbon coating to obtain a silicon-carbon composite material. The thickness of the carbon coating layer of the silicon-carbon composite material is 30 nm.

[0092] Example 2

[0093] The difference from Example 1 is that in step S1, 400 g of zinc chloride is replaced by 350 g of zinc chloride and 50 g of Pluronic® F127. The remaining steps are the same as those in Example 1.

[0094] Example 3

[0095] The difference from Example 1 is that the weight of the carbon nanotubes in step S1 is changed to 5 g.

[0096] Step S2 is modified to place the spherical activated carbon precursor in a flash Joule heating device. The vacuum degree of the flash Joule heating is 1.2 Torr, the voltage of the flash Joule heating is set to 280 V, the temperature is raised to 1000°C in 1 second, and then the power is continuously turned on for 10 seconds. The equipment operates in an inert atmosphere of argon gas, and the activated carbon powder is collected after cooling to room temperature.

[0097] The remaining steps are the same as those in Example 1.

[0098] Comparative Example 1

[0099] The difference from Example 1 is that the flash Joule heating device in step S2 is replaced by a conventional rotary kiln heating, with a rotation speed of 10 Hz, a nitrogen flow rate of 0.4 L / min, and a heating rate of 5°C / min to 1000°C for 2 hours. The remaining steps are the same as in Example 1.

[0100] Comparative Example 2

[0101] S1. Compared with Example 1, only no carbon nanotubes were added.

[0102] S2. Since no carbon nanotubes were added, the conductivity of the resin balls was very poor and it was difficult to perform flash Joule heating. Therefore, a pre-carbonization step was added. The pre-carbonization step was to place the spherical activated carbon precursor in a rotary furnace at a speed of 10 Hz and a nitrogen flow rate of 0.4 L / min, and heat it to 500°C at a heating rate of 5°C / min, keep the temperature constant for 2 hours, and collect the spherical activated carbon precursor after cooling.

[0103] S3. Place the spherical activated carbon precursor in a flash Joule heating device with a vacuum degree of 1.2 Torr and a voltage of 350 V. Heat to 1000°C in 1 second and keep the power on for 10 seconds. The device operates in an inert atmosphere of argon and collects the activated carbon powder after cooling to room temperature.

[0104] S4. Same as steps S3 and S4 of Example 1.

[0105] Comparative Example 3

[0106] The difference from Example 1 is that the amount of zinc chloride in step S1 is increased to 800 g. The remaining steps are the same as those in Example 1.

[0107] Comparative Example 4

[0108] The difference from Example 1 is that the zinc chloride in step S1 is replaced by Pluronic® F127, and the amount used is increased to 800 g, and the remaining steps are the same as in Example 1.

[0109] Comparative Example 5

[0110] The difference from Example 1 is that the amount of zinc chloride in step S1 is reduced to 200 g. The remaining steps are the same as those in Example 1.

[0111] Comparative Example 6

[0112] The difference from Example 1 is that the weight of the carbon nanotubes in step S1 is changed to 15 g.

[0113] Step S2 is modified to place the spherical activated carbon precursor in a flash Joule heating device. The vacuum degree of the flash Joule heating is 1.2 Torr, the voltage of the flash Joule heating is set to 185 V, the temperature is raised to 1000°C in 1 second, and then the power is continuously turned on for 10 seconds. The equipment operates in an inert atmosphere of argon gas, and the activated carbon powder is collected after cooling to room temperature.

[0114] The remaining steps are the same as those in Example 1.

[0115] Effect Example

[0116] The silicon-carbon composite materials prepared in the above-mentioned Examples 1-3 and Comparative Examples 1-6 were tested for specific surface area, thermogravimetric and electrochemical properties.

[0117] (1) Specific surface area test

[0118] The specific surface areas of the silicon-carbon composite materials prepared in Examples 1-3 and Comparative Examples 1-6 were tested by the fully automatic specific surface area and pore size analysis NOVAtouchTM of Quantachrome Instruments, USA. The total pore volume was calculated based on the BJH adsorption and desorption model, and the average pore size was calculated based on the NLDFT model. The specific test results are shown in Table 1.

[0119] (2) Raman test

[0120] The Raman spectra of the silicon-carbon composite materials prepared in the above Examples 1-3 and Comparative Examples 1-6 were respectively tested using a Thermo Fischer DXR Raman spectrometer, and the graphitization degree of the samples was evaluated by calculating the D peak to G peak intensity ratio to obtain Id / Ig.

[0121] Table 1 Physical and chemical properties of activated carbon in Examples and Comparative Examples

[0122]

[0123] (3) Silicon content test

[0124] The silicon content of the silicon-carbon composite materials obtained in the above-mentioned Examples 1-3 and Comparative Examples 1-6 was tested respectively. The test method is to heat the sample to 1200°C at a heating rate of 1°C / min in air, and measure it by thermogravimetric analysis. The thermogravimetric analyzer used is Mettler Toledo TGA2 (SF) model. During the thermogravimetric analysis process, the carbon material is completely burned in the air to generate CO2, and the silicon in the material is completely oxidized to SiO2. By comparing the molecular weight, the mass of the remaining SiO2 is calculated, and it is converted into the mass of silicon (Si), and finally divided by the total weight of the original sample to obtain the silicon content. The specific test results are shown in Table 2.

[0125] (4) Electrochemical performance test

[0126] The silicon-carbon composite material, conductive carbon black and polyacrylic acid prepared in the above-mentioned embodiments 1-3 and comparative examples 1-6 were dispersed in water in a mass ratio of 7:2:1 to prepare a slurry, which was coated on a copper foil, dried at 70°C, rolled and cut into a pole piece with a diameter of 12 mm as an anode, a metal lithium sheet as a cathode, and a 1 mol / L LiPF6 three-component mixed solvent in a volume ratio of ethyl carbonate: dimethyl carbonate: methyl ethyl carbonate = 1:1:1 mixed electrolyte. The diaphragm was Celgard 2400, and the 2032 button battery was assembled in a glove box filled with argon. The electrical performance test was carried out in the LAND battery test system of Wuhan Landian Electronics Co., Ltd.

[0127] The test conditions for the first reversible capacity and first coulombic efficiency of the battery are: at room temperature, charge and discharge at a constant current of 0.1C, and the charge and discharge voltage is limited to 0.005-1.5V. The specific test results are shown in Table 2.

[0128] (5) Rate performance test

[0129] Under the same test conditions as the electrochemical performance test, the 2032 button cells obtained from the silicon-carbon composite materials of Examples 1-3 and Comparative Examples 1-6 were first subjected to two cycles of 0.1C constant current charge and discharge cycles, and then cycled 5 times at 0.2C, 0.5C, 1C, and 2C discharge rates, to obtain the capacities at the corresponding rates. The specific test results are shown in Table 2.

[0130] (6) Expansion rate test

[0131] Under the same test conditions as the electrochemical performance test, the expansion rate was measured by dividing the thickness of the electrode sheet of the 2032 button battery obtained from the silicon-carbon composite materials of Examples 1-3 and Comparative Examples 1-6 after 1.5 cycles by the original electrode sheet thickness and then multiplying by 100%. The specific test results are shown in Table 2.

[0132] Table 2 Electrochemical properties of silicon-carbon composite materials of Examples and Comparative Examples

[0133]

[0134] By comparing the results of Example 1 with Comparative Example 1, it can be seen that the activated carbon prepared by flash Joule heating has obvious advantages over the activated carbon prepared by the traditional rotary kiln. Specifically, the specific surface area is larger, the average pore size is smaller, and the pore size concentration is higher. These advantages come from the ultra-fast heating rate during the flash Joule heating process, which leads to the generation of finer zinc droplets and promotes the reaction with carbon. After high-temperature evaporation, more fine micropores are formed. In addition, the Id / Ig value of Example 1 is larger, indicating that the carbon structure of the material is more disordered, and more micropores provide a larger surface area, thereby supporting the deposition of more silicon. Moreover, compared with Comparative Example 1, Example 1 has improvements in both the first reversible capacity and the Coulomb efficiency.

[0135] Continue to compare Example 1 with Comparative Example 2 to analyze the key role of carbon nanotubes in the preparation of activated carbon materials and silicon-carbon finished products by flash Joule. First, since no carbon nanotubes were added to Comparative Example 2, the conductivity of the resin balls obtained by spray drying was poor, so the pre-carbonization process must be added. Continue to compare Example 1, Comparative Example 2, and Example 3. During the flash Joule heating process, although the three are heated to the same temperature, the voltage required for Comparative Example 2 and Example 3 is higher, and the energy consumption is also greater. Moreover, the more carbon nanotubes are added, the larger the specific surface area and pore volume of the activated carbon precursor are obtained. This is because the carbon nanotubes themselves have a large surface area, and their unique tubular structure is likely to promote the penetration and reaction of the activator to the carbon source. When the activator reacts with the carbon source at high temperature, it can use the surface and pores of the carbon nanotubes to help form a more stable and uniform pore structure. These activated carbons are applied to a gas-phase silicon-carbon matrix, and after silicon deposition and carbon coating, a silicon-carbon finished product is obtained. In contrast, Example 1 with added carbon nanotubes is significantly better than Example 3 with less added amount and Comparative Example 2 without added carbon nanotubes in terms of rate performance and expansion rate. This difference can be attributed to the excellent conductive properties of carbon nanotubes and the network structure formed. However, it is worth noting that when the content of carbon nanotubes in Comparative Example 6 is increased to 15g, the specific surface area of ​​the prepared activated carbon is reduced. Although the rate performance of the silicon-carbon finished product obtained is higher, the capacity and efficiency are reduced. When the content of carbon nanotubes in Example 1 continues to increase to 20g, entanglement and crosslinking are easily generated between the carbon nanotubes, resulting in nozzle clogging during spray drying.

[0136] By comparing Comparative Example 3 with Comparative Example 4, it is found that the pore-forming effects of different activators are different under the same mass ratio of activator dosage. Compared with the soft template F127, zinc chloride pore-forming can create more micropores and have a larger specific surface area. At the same time, zinc chloride can also catalyze the graphitization of the sample and reduce the Id / Ig value, which is beneficial to improve the electronic conductivity. In the silicon-carbon finished product, Example 1 activated with zinc chloride has more micropores and stronger adsorption, and can deposit more silicon, with a silicon content of 46.3 wt%, and shows a higher first reversible capacity (1788.7 mAh / g). In addition, when Example 1 and Example 2 are compared, when zinc chloride and F127 are synergistically activated, better effects can be obtained than using zinc oxide alone, and a larger specific surface area and pore volume can be achieved. Although the increased specific surface area cannot significantly increase the loading of silicon, the increased pore volume can improve the ion wettability and additional buffer space, so the final rate and expansion rate of the silicon-carbon sample can be significantly improved.

[0137] In addition, the pore structure of activated carbon can be effectively changed by adjusting the amount of pore-forming agent in the present invention. Compared with Example 1, the amount of zinc chloride in Comparative Example 3 increases, resulting in an increase in the average pore size of the activated carbon, but a decrease in the specific surface area, a decrease in the deposited silicon content, and a decrease in the first reversible capacity and coulombic efficiency. However, the expansion rate of Comparative Example 3 is significantly reduced, which is due to the reduction in silicon content on the one hand and the larger pore volume and pore size on the other hand. These changes help to provide more pores to buffer the expansion of silicon. Compared with Implementation 1, the amount of zinc chloride in Comparative Example 5 is reduced, resulting in a significant decrease in the specific surface area of ​​the activated carbon, a decrease in the deposited silicon content, and a decrease in the first reversible capacity and coulombic efficiency.

Claims

1. A method for preparing activated carbon, characterized in that: It includes the following steps: S1. spray drying a suspension of carbon nanotubes, an activator and a resin raw material to obtain an activated carbon precursor; Wherein, the mass ratio of the carbon nanotubes to the resin raw material is (0.4-1.2):40; Wherein, the mass ratio of the activator to the resin raw material is (30-60):40; S2. Performing flash Joule heating on the activated carbon precursor.

2. The method for preparing activated carbon according to claim 1, characterized in that: The activator is a metal zinc salt and / or a polymer template agent; Preferably, the metal zinc salt comprises a combination of one or more of zinc acetate, zinc chloride, zinc oxide and zinc acetylacetonate; Preferably, the polymer template comprises one or more combinations of polystyrene, PEO-PPO-PEO triblock copolymer, PS-P4VP diblock copolymer, polyethylene oxide PEO, polyvinyl pyrrolidone PVP, polymethyl methacrylate PMMA and polyvinyl alcohol PVA; Wherein, the PEO-PPO-PEO triblock copolymer is preferably a combination of one or more of Pluronic® F127, Pluronic® P123 and Pluronic® F108; Preferably, the activator is zinc acetate or Pluronic® F127; And / or, the resin raw material is a combination of one or more of phenolic resin, polystyrene, polyacrylonitrile, resorcinol-formaldehyde resin and polyimide, for example, phenolic resin; And / or, the solvent of the suspension of the carbon nanotubes, the activator and the resin raw material is a combination of one or more of anhydrous ethanol, NN dimethylamide, dimethyl sulfoxide, toluene and pure water, for example, anhydrous ethanol; And / or, the diameter of the carbon nanotube is 0.5-10 nm, preferably 1-2 nm; And / or, the length of the carbon nanotubes is 1 μm-30 μm, preferably 5-15 μm; And / or, the mass ratio of the carbon nanotubes to the resin raw material is (0.5-1.0): 40; And / or, the mass ratio of the activator to the resin raw material is (40-60):

40.

3. The method for preparing activated carbon according to claim 1, characterized in that: In the suspension, the volume ratio of solid to liquid is 5%-30%, for example 20%; and / or, the inlet air temperature of the spray drying is 80-200° C., for example 130-200° C.; And / or, the outlet air temperature of the spray drying is 60-100°C, such as 80-100°C; And / or, the feed rate of the spray drying is 0.01-1 L / h, preferably 0.5 L / h; And / or, the spray drying atmosphere is compressed air or an inert atmosphere; Preferably, the inert atmosphere is a combination of one or more of nitrogen, argon and helium; and / or, the spray-dried droplets have a D50 of 10-100 μm, such as 70 μm; and / or, the D10 of the activated carbon precursor is 1.5-5 μm, for example 3.2 μm; and / or, the D50 of the activated carbon precursor is 3-15 μm, for example 4.7 μm; and / or, the D90 of the activated carbon precursor is 5-50 μm, for example 6.5 μm; And / or, the activated carbon precursor is spherical; And / or, in the activated carbon precursor, the interior of the resin raw material contains a number of the carbon nanotubes, and the surface of the resin raw material contains a network structure formed by a number of the carbon nanotubes.

4. The method for preparing activated carbon according to claim 1, characterized in that: The end point temperature of the flash Joule heating is 800-3500° C., for example, 1000° C.; And / or, the voltage of the flash Joule heating is 50-400V, for example 200V; And / or, the flash Joule heating rate is 1000-8000°C / s; And / or, the continuous power-on time of the flash Joule heating is 0-100s, for example 10s; And / or, the atmosphere of the flash Joule heating is a vacuum or inert atmosphere; Preferably, the inert atmosphere is a combination of one or more of argon, nitrogen, helium and neon, such as argon; Preferably, the vacuum degree of the flash Joule heating is 1mTorr-10Torr, for example 1.2Torr; And / or, the flash Joule heating reaction equipment is a Joule heat tube furnace.

5. An activated carbon, characterized in that The activated carbon is prepared by the preparation method according to any one of claims 1 to 4; Preferably, the specific surface area of ​​the activated carbon is 1450-1900m 2 / g, such as 1459.7, 1520.1, or 1812.8m 2 / g; Preferably, the total pore volume of the activated carbon is 1.0-1.2 cm 3 / g, such as 1.02 or 1.15 cm 3 / g; Preferably, the average pore size of the activated carbon is 0.8-1.8 nm, such as 0.83, 0.88 or 1.76 nm.

6. A method for preparing a silicon-carbon composite material, characterized in that: Specifically comprising the following steps: vapor-depositing the activated carbon and silicon source as claimed in claim 5; Preferably, the silicon-carbon composite material includes the activated carbon and the silicon source deposited in the pores of the activated carbon.

7. The method for preparing the silicon-carbon composite material according to claim 6, characterized in that: The method for preparing the silicon-carbon composite material satisfies one or more of the following conditions: (1) The silicon source is in gaseous state; (2) The silicon source is a combination of one or more of monosilane, disilane and silane derivatives, such as monosilane; (3) The flow rate of the silicon source is 0.1-30 L / min, for example 0.8 L / min; (4) The atmosphere for the vapor deposition is an inert atmosphere; Preferably, the inert atmosphere is a combination of one or more of nitrogen, argon and helium, such as argon; Preferably, the flow rate of the inert atmosphere is 0.1-40 L / min, for example 0.4 L / min; (5) The reaction equipment for the vapor deposition is a rotary kiln or a fluidized bed, such as a fluidized bed; (6) The reaction temperature of the vapor deposition is 400-700°C, for example 600°C; (7) The reaction time of the vapor deposition is 2-12 hours, for example 5 hours or 10 hours; (8) The heating rate from room temperature to the reaction temperature of the vapor deposition is 1-5°C / min, for example 3°C / min; (9) The gas pressure of the vapor deposition is 100-11000 Pa, for example 1 MPa.

8. The method for preparing the silicon-carbon composite material according to claim 6, characterized in that: After the vapor deposition, a carbon coating step is also included; Preferably, the carbon source used for the carbon coating is a hydrocarbon mixture, more preferably a combination of one or more of methane, ethane, propane, isopropane, butane, isobutane, ethylene, propylene, acetylene, butene and natural gas, such as acetylene; Preferably, the flow rate of the carbon source used for the carbon coating is 0.1-40 L / min, for example 0.2 L / min; Preferably, the carbon coating atmosphere is an inert atmosphere, and the inert atmosphere is more preferably a combination of one or more of nitrogen, argon and helium, such as argon; More preferably, the flow rate of the inert atmosphere is 0.1-40 L / min, for example 0.4 L / min; Preferably, the carbon coating method is gas phase coating; Preferably, the carbon coating reaction temperature is 400-700°C, for example 600°C; Preferably, the carbon coating reaction time is 2-24h, such as 3h or 6h; Preferably, after the carbon coating, the thickness of the carbon coating layer of the obtained silicon-carbon composite material is 2-50 nm, for example, 30 nm.

9. A silicon-carbon composite material, characterized in that: It is prepared by the preparation method of the silicon-carbon composite material according to any one of claims 6 to 8; Preferably, the silicon content of the silicon-carbon composite material is 44-53 wt%, such as 51.9, 52.2 and 52.4 wt%.

10. Use of the silicon-carbon composite material as claimed in claim 9 in preparing battery pole pieces.

Citation Information

Patent Citations

  • Preparation method of coal-based porous carbon

    CN113307267A

  • A porous carbon double bond modified silane deposition anode material, its preparation method and application

    CN114122370B

  • Porous carbon material based on high-temperature thermal shock carbonization and KOH activation of coconut shell material, preparation method and application

    CN114408919A

  • Carbon fiber microsphere-nano silicon composite material and preparation method thereof

    CN117038989A

  • Method for preparing carbon nanospheres through Joule thermal flash evaporation and application

    CN117585667A

Cited By

  • Carbon nanotube modified phenolic resin and application thereof in porous carbon and silicon carbon

    CN121045734A